THU0539 Population-Specific Resequencing Reveals Association of The ABCC4/MRP4 Gene with Gout in New Zealand Māori and Pacific Men. (15th July 2016) - Merriman, T.; Boocock, J.; Stahl, E.; Cadzow, M.; Phipps-Green, A.; Topless, R.; Harre Hindmarsh, J.; Mount, D.; Stamp, L.; Dalbeth, N.; Choi, H.; Tanner, C.
Abstract : Background: Genetic variants in uric acid transporters that control serum urate levels have been identified in Europeans by genome-wide association studies [1]. However there is no evidence for association with serum urate (or gout) with the organic anion transporters (OAT) 1–3 ( SLC22A6, SLC22A7 and SLC22A8 ) and multi-drug resistance protein 4 (MRP4) encoded by ABCC4 ; all four transporters have been implicated in uric acid secretion [2]. The Māori and Pacific (Polynesian) population of New Zealand (NZ) has the highest prevalence of gout worldwide and exhibits lower fractional excretion of uric acid (FEUA) than Europeans. Objectives: To identify any Polynesian population-specific genetic variants in the SLC22A6–8 and ABCC4 genes associated with gout. Methods: All participants had ≥3 self-reported Māori and/or Pacific grandparents. From the total sample set of 1808 individuals, 191 hyperuricaemic (highest urate levels) and 202 normouricaemic (lowest urate levels) individuals were selected and resequenced over a total of 24.3 kb of promoter, exon and 3' and 5' untranslated region DNA within the four genes. Replication genotyping for rs4148500 was done using Taqman over the remaining 1415 individuals. Logistic regression association analysis with gout or hyperuricaemia (≥0.36 mmol/L in women, ≥0.42 mmol/L in men) as outcome, or linear regression with FEUA or serum urate as outcome, was performed adjusting by age, sex and Polynesian ancestry. Results: A total of 39 common variants were detected with one in ABCC4 ( rs4148500 ) significantly associated with hyperuricaemia and gout. There were substantial differences in allele frequency between Western (Samoan, Tongan, Niuean, Tokelaun) and Eastern (NZ and Cook Island Māori) Polynesian samples – adjusting for ancestry revealed evidence for association with gout in the resequenced samples (OR=1.62, P =0.012 for rs4148500 ). The association of rs4148500 with gout was replicated (OR=1.25, P =0.033) and was restricted to males (ORMales =1.43, P =0.001; ORFemales =0.98, P =0.89). The gout risk allele was associated with FEUA in males (b=-0.570, P =0.01) and there was a trend towards association with serum urate in the male controls (b=0.013, P =0.07). The Ensembl database revealed that the variant was monomorphic (for the protective major allele) in Europeans. Conclusions: This is the first report of a genetic factor specifically contributing to the increased risk of gout in men of Māori and Pacific ancestry in NZ. Association of ABCC4 with gout and FEUA is consistent with the established role of MRP4 as a unidirectional urinary uric acid efflux pump of uric acid [3]. References: Kottgen et al. Nat Genet 2013;45:145 Mandal and Mount. Ann Rev Physiol 2015;77:323 Van Aubel et al. Am J Physiol 2005;288:F327 Acknowledgement: The New Zealand Health Research Council, Lottery Health New Zealand, Arthritis New Zealand and the National Institute of Health (United States) are thanked for funding this study. Disclosure of Interest: T. Merriman Grant/research support from: ArdeaBio, J. Boocock: None declared, E. Stahl: None declared, M. Cadzow: None declared, A. Phipps-Green: None declared, R. Topless: None declared, J. Harre Hindmarsh: None declared, D. Mount: None declared, L. Stamp: None declared, N. Dalbeth Grant/research support from: Fonterra, ArdeaBio, AstraZeneca, Consultant for: Takeda, Menarini, Teijin, Pfizer, Crealta, Cymabay, H. Choi: None declared, C. Tanner: None declared